PENGEMBANGAN PEMAHAMAN AS-SUNNAH SEBAGAI SUMBER AJARAN ISLAM - Sutoyo, Sutoyo (Jurnal THEOLOGIA, 2011)
Abstract: The second source of Islamic Law is as-Sun¬nah, because the first one is al-Qur’an which is considered still global. The global one needs explaination and interpretation. The Existence of as-Sunnah is really required in order that the moslems are able to understand and to im¬ple¬ment wholistically. Although the existence of al-Sunnah in ulemas is debated, some agree while others disagree. Several ulemas even refu¬se al-Sunnah as the second Islamic Law Source (they don’t follow al-Sunnah) with several ar¬guments. However, majority, the ulemas accept and agree to place as-Sunnah as the second Islamic law source. From majority, ulemas agree to place as-Sunnah as the second Islamic Law Source is also different from the usage of it. Some use as-Sunnah wholistically and some use as-Sunnah which is evaluated valid. To under¬stand and to give the meaning of as-Sunnah for ulemas of Muḥadiṡīn and Uṣūliyin. It is also different. Ulemas of Muḥadiṡīn give the meaning of as-Sunnah and al-ḥadīṡ similar that which comes wholistically from the prophet as what he said, he did and the decision (taqrir) of the prophet before and after bi’tsah (to be assigned as the prophet). Whereas the ulemas of usuliyin differ al-Sunnah and al-hadis. According to them, if all of them comes from the prophet said, did, and taqrir. It is named as al-Sunnah, if it is what to be said only by the prophet or qauliyah, it is named as al-hadis. Kata kunci: as-Sunnah, al-Ḥadīṡ, al-Khabar, al-Aṡar